Ownership structure and profitability of listed firms in an emerging market - Richard Angelous Kotey; Baah Kusi; Richard Akomatey (Growing Science. Accounting, 2019)
Motivated by the agency theory and the need to examine the effect of separation of ownership and management, this study examines the determinants of profitability in different firm ownership structures and how different ownership structures impact the profitability of listed firms between 2003 and 2013, using pooled annual data of 23 Ghanaian listed firms. Employing a number of static models (OLS, Random Effects and 3 Stage Least Squares), we find evidence that while profit determinants vary for listed firms given their ownership structures, ownership structures also affected profitability differently. Specifically, for listed firms, profitability was determined by capital intensity, liquidity, financial risk, age and GDP; for non-family owned listed firms, profitability was determined by capital intensity, liquidity, market share and age; for foreign-owned firms, profitability was determined by capital intensity, liquidity, age and GDP; and for non-foreign ownership, profitability was determined by capital intensity, liquidity, financial risk, growth, age and GDP. When we examine the impact of ownership structure on profitability and find that family-owned listed firms make 30% less profits compared to nonfamily owned ones, whilst foreign-owned firms make 13% more profits than non-foreign owned ones. These findings confirm the agency theory which posits that separation of ownership and management, though may lead to agency problems, can positively affect profits. The study recommends that family-owned listed firms should consider diluting ownership in order to grow more profits.
Keywords: G32; C23; L25; 330; Ownership structure; Profitability; Listed firms; Ghanaian firms